Monitoring Spinal Cord Tissue Oxygen in Patients With Acute, Severe Traumatic Spinal Cord Injuries - Visagan, Ravindran; Hogg, Florence R A; Gallagher, Mathew J; Kearney, Siobhan; Zoumprouli, Argyro; Papadopoulos, Marios C; Saadoun, Samira (Critical care medicine, 2022)
To determine the feasibility of monitoring tissue oxygen tension from the injury site (pscto2) in patients with acute, severe traumatic spinal cord injuries. We inserted at the injury site a pressure probe, a microdialysis catheter, and an oxygen electrode to monitor for up to a week intraspinal pressure (ISP), spinal cord perfusion pressure (SCPP), tissue glucose, lactate/pyruvate ratio (LPR), and pscto2. We analyzed 2,213 hours of such data. Follow-up was 6-28 months postinjury. Single-center neurosurgical and neurocritical care units. Twenty-six patients with traumatic spinal cord injuries, American spinal injury association Impairment Scale A-C. Probes were inserted within 72 hours of injury. Insertion of subarachnoid oxygen electrode (Licox; Integra LifeSciences, Sophia-Antipolis, France), pressure probe, and microdialysis catheter. pscto2 was significantly influenced by ISP (pscto2 26.7 ± 0.3 mm Hg at ISP > 10 mmHg vs pscto2 22.7 ± 0.8 mm Hg at ISP ≤ 10 mm Hg), SCPP (pscto2 26.8 ± 0.3 mm Hg at SCPP < 90 mm Hg vs pscto2 32.1 ± 0.7 mm Hg at SCPP ≥ 90 mm Hg), tissue glucose (pscto2 26.8 ± 0.4 mm Hg at glucose < 6 mM vs 32.9 ± 0.5 mm Hg at glucose ≥ 6 mM), tissue LPR (pscto2 25.3 ± 0.4 mm Hg at LPR > 30 vs pscto2 31.3 ± 0.3 mm Hg at LPR ≤ 30), and fever (pscto2 28.8 ± 0.5 mm Hg at cord temperature 37-38°C vs pscto2 28.7 ± 0.8 mm Hg at cord temperature ≥ 39°C). Tissue hypoxia also occurred independent of these factors. Increasing the Fio2 by 0.48 increases pscto2 by 71.8% above baseline within 8.4 minutes. In patients with motor-incomplete injuries, fluctuations in pscto2 correlated with fluctuations in limb motor score. The injured cord spent 11% (39%) hours at pscto2 less than 5 mm Hg (< 20 mm Hg) in patients with motor-complete outcomes, compared with 1% (30%) hours at pscto2 less than 5 mm Hg (< 20 mm Hg) in patients with motor-incomplete outcomes. Complications were cerebrospinal fluid leak (5/26) and wound infection (1/26). This study lays the foundation for measuring and altering spinal cord oxygen at the injury site. Future studies are required to investigate whether this is an effective new therapy.